FINANCIAL PERFORMANCE ANALYSIS OF FOOD AND BEVERAGE COMPANIES ON THE INDONESIA STOCK EXCHANGE - Annisa, Nurul; Masruddin, Masruddin; Iqbal, Moh.; Pakawaru, Muhammad Ilham (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to describe, analyze, interpret and describe how good or bad the financial performance of companies & Beverages listed on the Stock Exchange from 2019 to 2023. The measurement of financial performance in this study uses the financial ratio analysis method, with the current ratio method on the liquidity ratio, the total debt to asset ratio method on the Solvency Ratio and the Net return on asset method on the Profitability Ratio. And as a result, the food and beverage industry sector has become the mainstay of industrial production growth. The population of this study were 13 food and beverage companies listed on the Indonesia Stock Exchange during the 2010-2023 observation period. The sampling method used was purposive sampling, so that 9 sample companies were obtained for 5 years of observation from 2019 to 2023. The data obtained from the annual reports of sample companies downloaded from the IDX website, namely www.idx.co.id and the official website.